Pengaruh Lovemarks dan Brand Satisfaction terhadap Brand Loyalty Wisatawan Domestik yang Mengunjungi Destinasi Wisata Super Prioritas Danau Toba - Stefanie, Dewi; Susianti, Hartanti Woro; Widana, Ida Bagus Gede Agung (Journal of Applied Science in Tourism Destination, 2024)
This study was conducted with the aim of determining the influence of lovemarks and brand satisfaction on the brand loyalty of domestic tourists visiting Lake Toba Super Priority tourist destinations, the data used was quantitative with primary and secondary data sources. This study uses simple linear regression analysis techniques to determine the influence of variables partially and also multiple regression analysis techniques to determine the influence of variables simultaneously. The sampling technique used is purposive sampling with a sample of 100 who have the criteria of having visited Lake Toba Super Priority tourist destinations at least 2 times in the last 5 years. The results of this study show that there is a significant positive influence of lovemarks and brand satisfaction on the brand loyalty of domestic tourists who visit Lake Toba's Super Priority tourist destinations partially and simultaneously. The coefficient of determination (R-Square) obtained simultaneously is 0.394 which means that 39.4% of tourist brand loyalty visiting Lake Toba Super Priority tourist destinations is influenced by lovemarks and brand satisfaction variables. Therefore, the remaining 60.6% of tourist loyalty who visit Lake Toba's Super Priority tourist destinations is influenced by other variables that were not studied in this study.